Pengaruh Disiplin Kerja, Motivasi Kerja dan Kompensasi terhadap Kinerja Tendik pada UAD Yogyakarta - Yeni Lestari; Ema Nurmaya; Abdul Choliq Hidayat (Syntax Idea)
This study aims to determine the influence of Work Discipline, Work Motivation, and Compensation on the performance of all permanent academic staff employesss as UAD Yogyakarta. The population of this study consists of all staff members in campus one, campus two, campus three, campus four, and campus five at UAD Yogyakarta. The sample measurement technique uses the Slovin formula because the population is known with certainty. The sample in this study consists of 197 staff members at UAD Yogyakarta. The sampling technique used is random sampling as a method of data collection. Hypothesis testing is conducted using multiple linear regression analysis using SPSS. The results of the study indicate that Work Discipline has a positive and significant effect on performance, Work Motivation has a positive and significant effect on performnce, and Compensation has a positive and significant effect on performance. The three variabels, Work Discipline, Work Motivation, and Compensation, simultaneously have a positive and significant effect on performance. The results of this study are expected to contributi to the theory and practice of organizations in improving performance.